Water and physiological relationships of lettuce cultivated in hydroponics with brackish waters - Soares, Hammady; Santos Júnior, José; Silva, Ênio; Rolim, Mário; Silva, Gerônimo (Revista Ciência Agronômica, 2019)
Rationalization of brackish water management in hydroponic crops is one of the ways to expand and manage water supply in shortage areas. Thus, this work was carried out to evaluate the water and physiological relationships of Iceberg lettuce (cv. Tainá) in plants exposed to strategies of replacement of the evapotranspired volume of saline nutrient solutions. Two experiments were conducted in NFT hydroponic system, in which increasing levels of water salinity (0.2, 1.2, 2.2, 3.2, 4.2 and 5.2 dS m-1) were used to prepare the nutrient solutions. In the first experiment, the evapotranspired volume was replaced with the respective brackish water and, in the second one, with public-supply water (0.2 dS m-1). Both experiments were set up in a randomized block design, with six treatments and four replicates, totaling 24 experimental plots. It was concluded that using brackish water to prepare the nutrient solution, regardless of whether the evapotranspired volume was replaced with brackish or public-supply water, affected lettuce water and physiological relationships. However, although it caused a reduction in size, the use of brackish water did not cause visual damages that would compromise the commercial appeal of the plants. It was also found that, when water of up to 5.2 dS m-1 was used to prepare the solution, the replacement of the evapotranspired volume with public-supply water increased water use efficiency by up to five times.